Association between composite dietary antioxidant index and kidney stone prevalence in adults: data from National Health and Nutrition Examination Survey (NHANES, 2007–2018) - Duan, Qixin; Huang, Han; Zhang, Shuang; Wang, Yang; Lu, Dongming; Wan, Lixin; Sun, Yingming; Wu, Yongyang (Frontiers in Nutrition, 2024)
The high prevalence of kidney stones in adults worldwide has prompted research into potential interventions, one of which involves exploring the consumption of antioxidants that may confer protective effects. However, the relationship between the comprehensive dietary antioxidant index (CDAI), a crucial measure used to assess an individual's overall antioxidant capacity from daily dietary intake, and kidney stones remains unclear. Therefore, we conducted cross-sectional analysis to examine the association between CDAI and kidney stone prevalence. Methods: The analysis was conducted utilizing data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Antioxidant intake was derived from two 24hour dietary recalls surveys, while CDAI, a comprehensive measure that includes antioxidants like vitamins A, C, and E, zinc, selenium, and carotenoids, was calculated. Multivariate logistic regression and restricted cubic spline (RCS) regression were utilized to examine the association between CDAI and the prevalence of kidney stones.The study included a total of 28,516 participants, with 2,748 individuals having a history of kidney stones. The median of CDAI was -0.01 (-2.02, 2.37). Individuals in the fourth quartile of CDAI exhibited a significantly lower prevalence of kidney stones compared to those in the first quartile (Odds Ratio [OR] = 0.769 [0.633-0.935]), even after adjusting for potential confounding factors (including age, sex, race, education level, poverty income ratio, smoking status, drinking status, body mass index (BMI), energy intake levels, physical activity level, serum calcium concentration, estimated glomerular filtration rate (eGFR), hypertension, diabetes and supplement use ). The RCS analysis revealed a non-linear relationship between CDAI and kidney stone prevalence, with inflection points identified at 0.06 (P for non-linearity = 0.039). Furthermore, a significant inverse correlation was observed between CDAI and inflammatory markers. Subgroup analysis demonstrated consistent CDAI-kidney stone prevalence associations across all subsets. Furthermore, a significant inverse correlation was observed between CDAI and inflammatory markers.This study provides evidence supporting a reciprocal correlation between adult dietary antioxidant intake,as measured by CDAI, and kidney stone prevalence. These findings emphasize the potential benefits of consuming dietary antioxidants in lowering the risk of kidney stone formation.